Challenging the incumbent: Entry in markets with captive consumers and taste heterogeneity - Christian Oertel; Armin Schmutzler (University of Zurich, Department of Economics, 2021)
We analyze entry of a firm with a new and differentiated product into a market with two properties: An existing incumbent has a captive consumer base, and all consumers have heterogeneous tastes. The interaction of the share of captive consumers with the degree of taste heterogeneity leads to non-monotone effects of both parameters on entry. In particular, a higher captive share can support entry when heterogeneity is low but not when it is high, and higher taste heterogeneity (i.e., less product substitutability) can impede entry in the presence of captive consumers. Considering these effects together leads to new insights on entry, horizontal product innovation, and price discrimination.
Keywords: L13; L40; 330; Entry; captive consumers; asymmetric competition; product innovation